APPLICATION AUDITORY LEARNING STYLE METHOD TO INCREASE STUDENTS ENTHUSIASM FOR LEARNING - Alifah, Alifah; Abdullah, Abdullah (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Education is an effort to improve the quality of life and human resources. One of the goals of education is to increase student creativity in learning at school. Creativity is an indicator of student success in the learning process which plays an important role in achieving learning goals. Learning style is a Learning style can be interpreted as a variety of ways in the learning process, it is also one of the important factors that influence learning achievement, but until now the learning style factor is often forgotten in the learning process. Not only by teachers but also by students themselves, where students' learning styles differ depending on their character or according to their own abilities, students are able to absorb lessons quickly, usually using a variety of learning methods. Therefore, there is a need for coaching and guidance for students to determine appropriate learning methods so that the learning process can run effectively. we will learn better and will also be more effective by listening more, because from listening it is easier for us to understand and remember. In this research we discuss how the way we learn will greatly influence the structure of the brain, this is what we then know as known learning styles. as an auditory learning style. The purpose of writing this article is to understand students' learning styles in order to make it easier and make students learn so they are not lazy. The method used is library research, collecting data by searching from various sources such as books, journals and existing research.